Improving student engagement in learning requirement engineering subject using pair learning - Mohd Sanusi, Nurazlina; Mohamad, Abdul Karim (Little Lion Scientific Islamabad Pakistan, 2025)
Requirement engineering is one of the disciplines in software engineering areas that play an important role in determining successful software development. Many researchers have highlighted the importance of requirement engineering aspects in software engineering. They pointed out that one of the difficulties of teaching requirement subjects is the preparation in the classroom to teach requirement engineering subject and make students engage. Learning requirement subject can be difficult for some students in the classroom. In this paper, we presented a new engagement framework using pair work learning in the classroom. We adapted pair work and explored this approach in teaching and learning requirement engineering subject. With the assistance of the learning management system (Moodle platform – in our university, we called ULearn), the activities and assessments designed in pair, we lead the students to linkage with engagement and lead them to learn.